2010
DOI: 10.1021/jp908202s
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for the Dynamic Adsorption of CO2 and CH4 in a Flexible Linear Chain Coordination Polymer as Determined from In Situ Infrared Spectroscopy

Abstract: Adsorption-desorption cycles for CO 2 and CH 4 on the one-dimensional coordination polymer, catenabis(dibenzoylmethanato)-(4,4′-bipyridyl)nickel(II), "Ni-DBM-BPY", showed pronounced step-shape isotherms, where minimal gas adsorption was detected below a threshold pressure and rapid gas uptake was observed above this threshold. Desorption isotherms from the saturated state displayed significant hysteresis from the adsorption isotherm path. Such behavior is rare in one-dimensional coordination polymers that lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 79 publications
1
26
0
Order By: Relevance
“…] gas ( 12 CO 2 ) [45] 667.3 1388.3 2349.3 gas ( 13 CO 2 ) [52] 649 1334 2283 silicalite [45,53] < 1 662 2341 PS [13] 657.2 2334.9 UiO-66 [22] 0.72 2340 UiO-66-NH 2 [22] 0.72 2337 UiO-66-NO 2 [22,54] 0.72 685, 669, 659, 649 2339 UiO-66-Br [22,54] 0.72 684, 669, 662, 657, 649 2338 MIL-53(Cr) [55,56] 11 669, 662, 650 2335 MIL-53(Al) [55] 661, 649 MIL-53(Al)-NH 2 [20] 200 669, 667, 661, 655, 649 2334 IRMOF-3 [14,20] 669, 667, 653 HKUST-1 2333 CPO-27-Mg [39] 2353 Ni-DBM-BPy [57] 2000 661, 645 2333 1288 www.chemsuschem.org cates that, upon interaction, the CO 2 bending mode is always followed by the splitting of the degenerate bending mode into two separate components. For the amines, a large variety of species have been considered in this study, which were selected by choosing those already reported in the literature and by proposing some new functionalities.…”
mentioning
confidence: 99%
“…] gas ( 12 CO 2 ) [45] 667.3 1388.3 2349.3 gas ( 13 CO 2 ) [52] 649 1334 2283 silicalite [45,53] < 1 662 2341 PS [13] 657.2 2334.9 UiO-66 [22] 0.72 2340 UiO-66-NH 2 [22] 0.72 2337 UiO-66-NO 2 [22,54] 0.72 685, 669, 659, 649 2339 UiO-66-Br [22,54] 0.72 684, 669, 662, 657, 649 2338 MIL-53(Cr) [55,56] 11 669, 662, 650 2335 MIL-53(Al) [55] 661, 649 MIL-53(Al)-NH 2 [20] 200 669, 667, 661, 655, 649 2334 IRMOF-3 [14,20] 669, 667, 653 HKUST-1 2333 CPO-27-Mg [39] 2353 Ni-DBM-BPy [57] 2000 661, 645 2333 1288 www.chemsuschem.org cates that, upon interaction, the CO 2 bending mode is always followed by the splitting of the degenerate bending mode into two separate components. For the amines, a large variety of species have been considered in this study, which were selected by choosing those already reported in the literature and by proposing some new functionalities.…”
mentioning
confidence: 99%
“…In recent years, National Energy and Technology Laboratory (NETL) has been one of the leading laboratories in the area of science and engineering research of novel Ni(CN) 4 -based flexible MOFs [56,[61][62][63][64][65]. The precursors of these flexible MOFs are typically a cyanometallate complex that acts as a ligand and a transition metal complex with available coordination sites.…”
Section: Ni(cn) 4 -Based Mofs (Picnics)mentioning
confidence: 99%
“…These compounds undergo cooperative spin transitions at high temperatures, and the host-guest interactions inside the pores have considerable effects on the spin crossover properties of these materials. Agusti et al [60] In recent years, National Energy and Technology Laboratory (NETL) has been one of the leading laboratories in the area of science and engineering research of novel Ni(CN)4-based flexible MOFs [56,[61][62][63][64][65]. The precursors of these flexible MOFs are typically a cyanometallate complex that acts as a ligand and a transition metal complex with available coordination sites.…”
Section: Ni(cn)4-based Mofs (Picnics)mentioning
confidence: 99%
“…[78] The catenabis(dibenzoylmethanate)-(4,4-bipyridyl)nickel(II) polymer (NiDBMBpy) compound was prepared by reaction of anhydrous bis(dibenzoylmethanato)nickel(II) (Ni(DBM) 2 ) with 4,4-bipyridine in dry tetrahydrofuran (THF) as previously described. [79] The ‡ Certain commercial materials and equipment are identified in this paper only to specify adequately the experimental procedure. In no case does such identification imply recommendation by NIST nor does it imply that the material or equipment identified is necessarily the best available for this purpose.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Thus, study of the contrasting structure transition mechanisms in NiBpene and NiDBM-Bpy can provide insights into how the nature of the structure transitions influences material performance. In this connection, and building on the previous structure characterizations [78,79] , an initial assessment of the crystal structure transitions…”
Section: Structural Changes Due To Adsorption and Desorption Of Guestmentioning
confidence: 99%